Kebijakan Penetapan Biaya Penyelenggaraan Ibadah Haji di Indonesia - Isabella, Isabella; Komar, Firdaus (Jurnal Pemerintahan dan Politik)
AbstractEvery year the interest of the Indonesian people to hajj continues to increase. In 2019 the number of Indonesian hajj will increase to 229,613 pilgrims. For this reason, appropriate policies are needed in making decisions in determining the amount of Hajj Operational Cost (BPIH) from Indonesia to Saudi Arabia. The study in this paper is a literature study of Political Economy. Political Economy is a theory or study of the role of public policy in influencing economic and social welfare in political relations (Merriam, 2018). According to Investopedia Political Economy is the study of production and trade, and its relation with costums, government and law. But in determining the amount of BPIH also influenced by many factors, such as world oil prices and the exchange rate of the rupiah. In relation to the determination of BPIH, this is inseparable from fiscal policy. Fiscal policy is a government instrument to influence the economy in the context of realizing national development, which is elaborated through the management of the National Budget (Republic of Indonesia, 2015). Fiscal policy is an economic policy carried out by the government in order to manage and direct economic conditions in a better or desired way by changing or updating government revenues and expenditures, one of the highlights of this fiscal policy is controlling government expenditure and revenue or countryKeywords : Policy, hajj, fiscalAbstrakSetiap tahun minat masyarakat Indonesia untuk menunaikan ibadah haji terus mengalami peningkatan. Tahun 2019 jumlah jamaah haji Indonesia meningkat menjadi 229.613 jamaah. Untuk itu diperlukan kebijakan-kebijakan yang tepat dalam pengambilan keputusan dalam menetapkan besaran Biaya Penyelenggaraan Ibadah Haji (BPIH) dari Indonesia ke Arab Saudi. Kajian dalam tulisan ini merupakan studi literatur Ekonomi Politik. Ekonomi Politik adalah teori atau studi tentang peran kebijakan publik dalam mempengaruhi kesejahteraan ekonomi dan sosial dalam kaitan politik (Merriam, 2018). Menurut Investopedia, Ekonomi Politik adalah studi tentang produksi dan perdagangan dan hubungannya dengan adat, pemerintah dan hukum. Dalam penentuan BPIH telah diatur sesuai dengan mekanisme yang ada di Indonesia. Namun dalam menetukan besaran BPIH juga dipengaruhi oleh banyak faktor, seperti harga minyak dunia dan kurs nilai tukar rupiah. Kebijakan fiskal merupakan instrumen Pemerintah untuk mempengaruhi perekonomian dalam rangka mewujudkan pembangunan nasional, yang dijabarkan melalui pengelolaan APBN (Republik Indonesia, 2015). Kebijakan fiskal adalah kebijakan ekonomi yang dilakukan oleh pihak pemerintah guna mengelola dan mengarahkan kondisi perekonomian ke arah yang lebih baik atau yang diinginkan dengan cara mengubah atau memperbarui penerimaan dan pengeluaran pemerintah, saalah satu hal yang ditonjolkan dari kebijakan fiskal ini adalah pengendalian pengeluaran dan penerimaan pemerintah atau Negara.Kata kunci : Kebijakan, haji, fiskal